(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In this article we are talking about pedagogical skill - a set of pedagogical qualities of a person and about ensuring the effective organization of professional pedagogical activity by a teacher, which is aimed at achieving the pinnacle of pedagogical skill.